Answer:
Therefore,
![Center\ is\ C(-3,3)\\and\\Radius= 2\ units](https://img.qammunity.org/2020/formulas/mathematics/middle-school/e71av23n8s0kl5psuv4ng8aepxtwlk0wcl.png)
Explanation:
Given:
A Equation of a Circle that is
![x^(2) +y^(2)+ 6x-6y=-14](https://img.qammunity.org/2020/formulas/mathematics/middle-school/enq1n9optys5rno00xcpw41s5iz0oykcyy.png)
Which can be written as
![x^(2) +y^(2)+ 6x-6y+14=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/adcnmyxuxasiwtii5mgikwfbgyy0r7752o.png)
To Find:
Center C( -g , -f ) = ?
radius = r =?
Solution:
General Equation of a Circle is given as
![x^(2) +y^(2)+ 2gx+2fy+c=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ntbbhqqotut0di7bwlxsdtgac3aa6yspf9.png)
On Comparing the Given equation with the General equation we get the following values,
![2g=6\ and\ 2f=-6\ and\ c=14\\\therefore g=(6)/(2)=3\\ \\\therefore f=(-6)/(2)=-3\\](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8memx4padt1wehgx11myeptu9ii6xjt35p.png)
Now, Center and Radius for above circle is given as
![C(-g,-f)=(-3,-(-3))=(-3,3)\\and\\radius = r=\sqrt{(g^(2)+f^(2)-c )} = \sqrt{(3^(2)+(-3)^(2)-14)}\\\\\therefore radius = r=√((18-14)) \\\\\therefore radius = r=√(4)=2\ unit\\](https://img.qammunity.org/2020/formulas/mathematics/middle-school/mu635ka04k33pqs61zod87d2ja9hb5sd06.png)
Therefore,
![Center\ is\ C(-3,3)\\and\\Radius= 2\ units](https://img.qammunity.org/2020/formulas/mathematics/middle-school/e71av23n8s0kl5psuv4ng8aepxtwlk0wcl.png)